Cash holdings in pension funds - Hasa, Sidita; Salva, Carolina (Journal of Banking & Finance, 2024)
Using unexplored data on Swiss pension funds, we document substantial heterogeneity in cash holdings across funds. While we identify key operational and investments needs to hold cash, they only explain a small share of the variation in cash holdings. A large share of this variation is attributable to an unobservable, time-invariant, fund-specific factor. The average fund holds excess cash and slowly deploys it for investment. Funds with excessive cash holdings keep 8.4% of total assets in excess cash. Investing this surplus in a representative portfolio, could yield an additional expected annual return of 17 to 32 basis points, ultimately benefiting pension participants. Finally, small funds have larger cash holdings that are less responsive to specific needs, suggesting greater potential for reducing cash allocations.